A Glimpse of Inflammation and Anti-Inflammation Therapy in Diabetic Kidney Disease - Liu, Chongbin; Yang, Ming; Li, Li; Luo, Shilu; Yang, Jinfei; Li, Chenrui; Liu, Huafeng; Sun, Lin (Frontiers in Physiology, 2022)
Diabetic kidney disease (DKD) is a common complication of diabetes mellitus and a major cause of end-stage kidney disease (ESKD). The pathogenesis of DKD is very complex and not completely understood. Recently, accumulated evidence from in vitro and in vivo studies has demonstrated that inflammation plays an important role in the pathogenesis and the development of DKD. It has been well known that a variety of pro-inflammatory cytokines and related signaling pathways are involved in the procession of DKD. Additionally, some anti-hyperglycemic agents and mineralocorticoid receptor antagonists (MRAs) that are effective in alleviating the progression of DKD have anti-inflammatory properties, which might have beneficial effects on delaying the progression of DKD. However, there is currently a lack of systematic overviews. In this review, we focus on the novel pro-inflammatory signaling pathways in the development of DKD, including the nuclear factor kappa B (NF-κB) signaling pathway, toll-like receptors (TLRs) and myeloid differentiation primary response 88 (TLRs/MyD88) signaling pathway, adenosine 5′-monophosphate-activated protein kinase (AMPK) signaling pathways, inflammasome activation, mitochondrial DNA (mtDNA) release as well as hypoxia-inducible factor-1(HIF-1) signaling pathway. We also discuss the related anti-inflammation mechanisms of metformin, finerenone, sodium-dependent glucose transporters 2 (SGLT2) inhibitors, Dipeptidyl peptidase-4 (DPP-4) inhibitors, Glucagon-like peptide-1 (GLP-1) receptor agonist and traditional Chinese medicines (TCM).